Mextex S.A. Estrategias administrativas: pequeñas empresas - Anzola Rojas, Sérvulo (1993)
It presents the case of a small business that faces a diverse problem at the internal and external levels, for which the manager requests the opinion of experts. It is provided information about production, finances, market, marketing strategies, distribution and sales; in addition to data related to personnel control and public relations. Among the causes of the company's difficulties seem to be the inadequate sales system, the dependence on a single customer, the poor organization of production and the little automated control system. It offers the student the opportunity to apply tools and techniques of a strategic nature, with an emphasis on planning and controlling, in a small or medium-sized company that lacks coordination and integration within each area and the company as a whole. To facilitate the analysis, a scheme is included for the formulation, identification and definition of a business strategy.